Atomic Force Microscopy Protocol for Measurement of Membrane Plasticity and Extracellular Interactions in Single Neurons in Epilepsy - Wu, Xin; Muthuchamy, Mariappan; Reddy, Doodipala Samba (Frontiers in Aging Neuroscience, 2016)
Physiological interactions between extracellular matrix (ECM) proteins and membrane integrin receptors play a crucial role in neuroplasticity in the hippocampus, a key region involved in epilepsy. The atomic force microscopy (AFM) is a cutting-edge technique to study structural and functional measurements at nanometer resolution between the AFM probe and cell surface under liquid. AFM has been incrementally employed in living cells including the nervous system. AFM is a unique technique that directly measures functional information at a nanoscale resolution. In addition to its ability to acquire detailed 3D imaging, the AFM probe permits quantitative measurements on the structure and function of the intracellular components such as cytoskeleton, adhesion force and binding probability between membrane receptors and ligands coated in the AFM probe, as well as the cell stiffness. Here we describe an optimized AFM protocol and its application for analysis of membrane plasticity and mechanical dynamics of individual hippocampus neurons in mice with chronic epilepsy. The unbinding force and binding probability between ECM, fibronectin-coated AFM probe and membrane integrin were strikingly lower in dentate gyrus granule cells in epilepsy. Cell elasticity, which represents changes in cytoskeletal reorganization, was significantly increased in epilepsy. The fibronectin-integrin binding probability was prevented by anti-α5β1 integrin. Thus, AFM is a unique nanotechnique that allows progressive functional changes in neuronal membrane plasticity and mechanotransduction in epilepsy and related brain disorders.